Blood Urea Nitrogen Constituent of Pregant Ewes - Isdoni Isdoni; Hera M.; Aryani Sismin S. (Media Veteriner, 1996)
The research on blood urea nitrogen constituent of pregnant ewes has been carried out at the Departement of Physiology and Pharmacology, Faculty of Veterinary Medicine. Bogor Agricultural University. Ten ewes with about the same body weight and also about the same times of parturation were used in this experiment. PGF-, injection were used to sinchronize oestrous of those ewes. Blood were collected twice a month from the jugular vein and itsmetabolite constituent were analyzed. using the procedure as described in the kit.This result showed that the concentration of blood urea nitrogen in pregnant ewes was higher than in nonpregnant (p